Living in the World of Fake News: High School Students' Evaluation of Information from Social Media Sites. Issue 4 (1st October 2020) - Johnston, Nicole
ABSTRACT: Information is increasingly being disseminated and accessed through social media. This study evaluated how high school students evaluate content on platforms such as Facebook and Twitter. Thirty-seven students from two different high schools in Western Australia (WA) completed a survey and series of eight activities that asked them to evaluate information (both visual and written) posted on social media sites. The results showed that students trust TV news more than social media. The results also showed that although students often recognised legitimate news sources versus opinion, they often fail to recognise bias when it relates to political or organisation affiliation. The students also did not verify accuracy or authority outside of the social media posts, trusted 'evidence' even when it was inaccurate, often did not recognise the verified tick and often failed to recognise that images and videos can be edited. This study has shown that media literacy instruction in schools needs to move away from the checklist approach of teaching how to evaluate information and move towards an instructional approach that focuses on the more critical thinking aspects of evaluation such as the source of the information, social and political bias and verifying evidence and information through multiple sources.